Perspective of CIGS-BIPV’s Product Competitiveness in China - Hui Kong; Zhufeng Yu; Jun Zhang; Yijie Han; Lin Wu; Hongsheng Wang; Jian Wang (International Journal of Photoenergy)
Copper indium gallium selenide (CIGS) thin-film battery has high photoelectric conversion efficiency, better spectral dispersion ability, and weak light-adsorption characteristics, as well as shape and size flexibility. CIGS-BIPV (building integrated photovoltaic) has attracted more and more research attention with the advantages of good curvature, form and color diversity, and broad application prospects. This paper uses the classical “Porter’s Five Forces Model” to make a preliminary analysis of the competitiveness of CIGS-BIPV products. A more specific competitiveness analysis model is further built with the index modeling method, and the competitiveness of CIGS-BIPV products is thoroughly analyzed from qualitative and quantitative perspectives. Six primary research indicators are used, i.e., safety index, building aesthetics index, economic index, energy-saving and environmental protection index, innovation index, and sales force index. The weight analysis of index modeling shows that compared with a glass curtain wall, exterior stone, and silica-based BIPV, CIGS-BIPV is characterized by high product competitiveness, acceptable cost, attractive appearance, environmental benignity, high technical quality, and certain economic benefits. The product competitiveness of CIGS-BIPV could be further enhanced through the construction and promotion of sales channels.